INOVASI PRODUK KOPI PADA UMKM DAMPAKNYA TERHADAP DAYA SAING KOPI THRU - Sri Utami; Nurjannah Nurjannah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the role of product innovation in increasing the competitiveness of coffee MSMEs, with a case study on Kopi Thru. In an era of increasingly tight business competition, MSMEs are required to continue to innovate in order to survive and thrive. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results of the study show that product innovation carried out by Kopi Thru including the development of flavor variants, attractive packaging, and technology integration in service contributes significantly to increasing customer loyalty and market expansion. This innovation also encourages increased operational efficiency and a stronger brand image amidst competition in the local coffee industry. In conclusion, product innovation is a key factor in increasing the competitiveness of coffee MSMEs, especially for Kopi Thru in maintaining its existence and business growth.